A STATUS REVIEW OF THE HYDROLOGICAL CHARACTERIZATION OF THE BASEMENT COMPLEX AQUIFERS IN TARABA STATE, N. E. NIGERIA - OKEKE, O.C; OMOKO, E.N. (IJRDO-Journal of Applied Science, 2017)
The availability and access to fresh water is an important issue all over the world. Groundwater constitutes the only reliable water supply for drinking and irrigation purposes. Recently there has been increased interest in ground water resources resulting from a combination of an increase in its development for public and domestic use; an increase in mining, agricultural, and industrial activities which might impact ground water quality; and an increase in studies of already contaminated aquifers. Decision-making agencies involved in these groundwater activities require studies of the aquifers to develop reliable information on the hydrologic properties and behaviour of aquifers and aquitards. Aquifer testing is a common tool used by hydrogeologists to characterize aquifers flow system boundaries. The most reliable type of aquifer test usually conducted is a pumping test. Pumping tests are a practical and reliable means of estimating aquifer hydraulic properties, well performance, yield, zone of influence of the well and boundary conditions. Proper pumping test practices greatly assist in the interpretation and the value of the pumping test data. This paper is a review of methods of pumping test analysis and use of hydraulic parameters obtained in characterization of aquifer. A case history of the use of pumping test analysis in aquifer characterization in some parts of Nigeria is also highlighted.